Strategi Digital Marketing Dalam Meningkatkan Penjualan Burgo Di Palembang - Tata Sutabri; Nailah Ramadhani Laboy; Putri Asyifah Vahlevi; Muhammad Rizki (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Burgo is a kind of vegetable rice cake commonly eaten for breakfast by the people of Palembang. Burgo is made from a mixture of rice flour and starch shaped like a pancake and then cut into pieces like rice cakes then doused with fish sauce. This food recipe has been around for a long time and has been passed down from generation to generation. Even now this burgo food has been traded in stalls or eating places that serve it. This research aims to increase burgo sales in Palembang by using digital marketing strategies and how they can manage the digital. The method used is a literature study by collecting data from scientific journals and articles related to digital marketing strategies and burgo sales in Palembang. The results showed that with the presence of Burgo cakes in the market and the ease of buying them, Burgo can be a product that is highly appreciated and favored by the younger generation and other circles of society, in addition to being a snack food product that can compete with other snacks. Promotional strategies with creative visual communication messages by creating posters accompanied by illustrations and graphics so that people can always remember the existence of this traditional cuisine in the future to create a modern impression. The use of modern style with a traditional touch aims to attract people, especially the younger generation, to be interested in buying traditional food products typical of Palembang, especially burgo and other traditional Palembang dishes. this may be popular among young people. And the purpose of this promotion is that people, especially the younger generation, know the existence of this burgo food and want to make it a daily snack through promotional campaigns, target audiences, design styles that the target audience likes and very easily reach the target.